2009
DOI: 10.1002/ppul.21026
|View full text |Cite
|
Sign up to set email alerts
|

IL1B polymorphisms modulate cystic fibrosis lung disease

Abstract: Summary Rationale: Variability in pulmonary disease severity is found in patients with cystic fibrosis (CF) who have identical mutations in the CF transmembrane conductance regulator (CFTR) gene. We hypothesized that one factor accounting for heterogeneity in pulmonary disease severity is variation in the family of genes affecting the biology of interleukin-1 (IL-1), which impacts acquisition and maintenance of Pseudomonas aeruginosa infection in animal models of chronic infection. Methods: We genotyped 58 sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…Further, this autoamplification can significantly promote IL-17A, IL-17F, and IL-22 production and downstream inflammation. These findings also have direct disease relevance to CF, because we have shown that IL-23 levels are correlated with active infection (15,38) and that IL-1␤ is highly expressed in CF airways, is expressed concurrently with IL-23 and IL-17 during infection (15,38), and is associated with more severe CF disease (5,6,8,36 (37) reported that in their model of acute P. aeruginosa pulmonary infection, early IL-17 production is responsible for control of infection, a finding that contrasts with our current and prior studies (14). We believe that this difference in findings and conclusions between our studies might be explained on the basis of experimental technique.…”
Section: Discussionmentioning
confidence: 78%
“…Further, this autoamplification can significantly promote IL-17A, IL-17F, and IL-22 production and downstream inflammation. These findings also have direct disease relevance to CF, because we have shown that IL-23 levels are correlated with active infection (15,38) and that IL-1␤ is highly expressed in CF airways, is expressed concurrently with IL-23 and IL-17 during infection (15,38), and is associated with more severe CF disease (5,6,8,36 (37) reported that in their model of acute P. aeruginosa pulmonary infection, early IL-17 production is responsible for control of infection, a finding that contrasts with our current and prior studies (14). We believe that this difference in findings and conclusions between our studies might be explained on the basis of experimental technique.…”
Section: Discussionmentioning
confidence: 78%
“…25 IL1B SNPs rs1143634 and rs1143639 showed a consistent association with lung disease severity in cystic fibrosis, suggesting that IL-1β is a clinically relevant modulator of the lung disease. 26 …”
Section: Infections Chronic Inflammationsmentioning
confidence: 97%
“…STAT3, IL1B and IFNGR1 as CF modifiers H Labenski et al carries the causative variant, followed by re-sequencing of contrasting haplotypes to describe the sequence variants for which cases and control differ comprehensively by the base (IFNGR1). Although modern high-throughput technology allows for genomewide scans using SNP, 43,44 microsatellites 45 or in-depth investigation of candidate genes with multiple SNPs, 27 reports of modifying variants that have been systematically mapped and functionally validated by means of modifier-genotype/patient's-phenotype correlation are still the exception in the CF modifier field. In the light of this, we admit that the direct correlation between the length of the intronic microsatellite STAT3Sat and STAT3 expression levels among F508del-CFTR homozygous patients was an unexpected finding by serendipity as STAT3Sat was purely genotyped to capture inherited variants of the candidate gene.…”
Section: Dbe Agarosementioning
confidence: 99%
“…48 The gold standard for genetic association studies has always been the replication of findings in different study populations. For IL1B, described recently as a modifier by a North-American consortium, 27 we have compared both studies (author's comment: by chance, the two SNPs rs1143634 (Levy et al) and rs1143643 (this work) differ by the last two digits only -discriminative ciphers have been underlined for your convenience). Levy et al 27 emphasize an association to SNPs rs1143634 and rs1143639 in IL1B while our data implicate rs3917356 and rs4848306 for an association with CF disease severity and detect a transmission disequilibrium at rs1143643 (Table 2).…”
Section: Dbe Agarosementioning
confidence: 99%